A potent small-molecule inhibitor of the DCN1-UBC12 interaction that selectively blocks cullin 3 neddylation. Issue 1 (December 2017) - Zhou, Haibin; Lu, Jianfeng; Liu, Liu; Bernard, Denzil; Yang, Chao-Yie; Fernandez-Salas, Ester; Chinnaswamy, Krishnapriya; Layton, Stephanie; Stuckey, Jeanne; Yu, Qing; Zhou, Weihua; Pan, Zhenqiang; et al.
Abstract The Cullin-RING E3 ubiquitin ligases (CRLs) regulate homeostasis of ~20% of cellular proteins and their activation require neddylation of their cullin subunit. Cullin neddylation is modulated by a scaffolding DCN protein through interactions with both the cullin protein and an E2 enzyme such as UBC12. Here we report the development of DI-591 as a high-affinity, cell-permeable small-molecule inhibitor of the DCN1–UBC12 interaction. DI-591 binds to purified recombinant human DCN1 and DCN2 proteins withK i values of 10–12 nM, and disrupts the DCN1–UBC12 interaction in cells. Treatment with DI-591 selectively converts cellular cullin 3 into an un-neddylated inactive form with no or minimum effect on other cullin members. Our data firmly establish a previously unrecognized specific role of the DCN1–UBC12 interaction for cellular neddylation of cullin 3. DI-591 is an excellent probe compound to investigate the role of the cullin 3 CRL ligase in biological processes and human diseases. Cullins are central components of the ubiquitin-proteosome system and are activated via a neddylation process mediated by the DCN1–UBC12 complex. Here, the authors develop a small molecule inhibitor of the DCN1–UBC12 interaction that specifically blocks cullin 3 neddylation and can be used to probe the cellular function of cullin 3.